Diversity and Mitochondrial CO1-Based Barcoding of Orthopteran Species of Bangladesh: Diversity and Mitochondrial CO1-Based Barcoding - Mazumdar, Santosh; Rahman, A S M Sharifur; Seymour, Mathew; Chowdhury, Mohammad Al-Baruni (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Recognizing the ecological and economic significance of Orthoptera species in Bangladesh, maintaining an up-to-date inventory of the species within the country becomes crucial. Building upon previous records, the current investigation places a central focus on documenting the taxonomic identity, species distribution, and evolutionary relationships of Orthoptera species in Bangladesh, employing the mitochondrial COI-based barcoding technique. The findings reveal a total of 13 orthopteran species across 13 genera and 9 families, with three species identified through barcoding. Notably, Phlaeoba sikkimensis is recorded as a first for the Bangladeshi entomofauna, highlighting its importance in local biodiversity. The comprehensive genetic data presented in this study significantly enhance our understanding of orthopteran diversity, facilitating the development of effective measures for their conservation and sustainable management, thus fostering a harmonious coexistence with these ecologically and economically valuable species. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 125-136, June-December 2024